The lives of a Filipino/a high school student anthology of personal essays on high school in the Philippines - Tolentino, Roland B.; Delos Reyes, Joselito D.; Jarin, Ferdinand Pisigan (University of Santo Tomas Publishing House, 2022)
"The essays are touching tributes to the multitudes coming into being as high school students, and to the lives prior to the addition of two years of schooling as mandated for global competitiveness. Ours was a simpler time when the public schools excelled, private education was more liberal; and when despite restrictions, young individuals were able to negotiate their tribulations, make do with what is available, and set forth their dreams that forever marked and guided us in our adult life."--Back cover.